The problems of stopping studies at the university - Atstupėnienė, Regina; Tiknevičienė, Irena (Lietuvos matematikos rinkinys, 2002)
The paper deals with the problems of higher mathematics studies of the first course of the Mechanical Faculty students, analyses the results of the test in mathematics and presents thė ways to improve the studies.